Penerapan Terapi Generalis Halusinasi Untuk Menurunkan Tingkat Halusinasi Pada Pasien Skizofrenia Di RSJD Dr.RM. Soedjarwadi Klaten - Fadhilah Intan Pratiwi; Sitti Rahma Soleman; Wahyu Reknoningsih (Pusat Riset dan Inovasi Nasional, 2023)
Background: Hallucinations are false perceptual distortions that occur in maladaptive neurobiological responses, sufferers actually experience sensory distortions as real things and respond to them (Pardede, 2020). Generalist therapy is the application of standard scheduled nursing care that is applied to patients with the aim of reducing the mental nursing problems being handled. (Livana et al., 2020).Objective: To find out the results of implementing Generalist Therapy to Reduce the Level of Hallucinations in Schizophrenic Patients at RSJD Dr.RM Soedjarwadi Klaten.Method: The method used was a case study research design, the sample used was 2 respondents, the research instrument used was the AHRS observation sheet which was carried out before and after Hallucination Generalist Therapy was carried out. Findings: Before Generalist Hallucination Therapy Mr. A was in the category of severe hallucinations while Mr. P was in the category of moderate hallucinations. After Generalist Hallucination Therapy Mr. A was in the category of seeding hallucinations while Mr. P was in the mild category. Implication: There was a decrease in the level of hallucinations after the Hallucination Generalist Therapy was carried out on Mr. A and Mr.P which was carried out for 3 meetings.